Similarities in client-clinician perceptions of subjective social status and its association to similarities in the quality of working alliance and client anxiety symptoms. (17th November 2021) - Nakash, Ora; Cruz-Gonzalez, Mario; Lincoln, Alisa K.; Banerjee, Souvik; Alegría, Margarita
Abstract: Objective: : Subjective social status (SSS) has largely been ignored within psychotherapy literature. We investigated the association between similarities in client-clinician perceptions of SSS, similarities in their report of the quality of working alliance, and resultant anxiety symptoms. Method: : Participants represented a primarily low-income, culturally diverse sample of 312 clients receiving care from 68 clinicians at 13 outpatient mental health clinics in the Northeastern United States between September 2013 and August 2016. As part of a larger randomized controlled trial, clients and clinicians completed the MacArthur Scale of subjective social status and the Working Alliance Inventory (WAI), and clients completed the Generalized Anxiety Disorder 7-item Scale (GAD-7). Results: : At the within-clinician level, client-clinician dyads with less similar perceptions of the client's SSS were characterized by less similar perceptions of their alliance, which in turn resulted in worsening anxiety symptoms. Conclusion: : Clinicians' correct perception of their clients' social status might be important for sharing a similar view of the client-clinician level of alliance, which can, in turn, contribute to lowering the client's anxiety symptoms.